Students' Perceptions of Using ChatGPT in Higher Education English Learning - Engelina Salainti; Nofry Frans; Vera Wahani (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
The integration of ChatGPT in English classrooms as an EFL has become a subject of increasing interest, with many investigations that highlight its benefits and challenges. In a positive aspect, ChatGPT is seen a a valuable tool in improving language learning. ChatGPT gives real-time feedback that improves students’ involvement and customizes the learning experience to individual needs. This study explored the higher education English learning students’ perceptions regarding the use of ChatGPT, examining the benefits and challenges. Utilizing a quantitative approach, the researcher gathered the data from an online questionnaire with 22 close-ended, in five-point Likert scale statements. A convenience sample of 55 higher education English learning students participated. The study has shown that the students appreciate the feedback that personalized feedback and the interesting character of ChatGPT, which motivates them to learn. For the teachers, ChatGPT offers opportunities to improve assessment and materials. Although ChatGPT gives some advantages to EFL learning, including the improvement in involvement and personalized feedback, ChatGPT raises concerns about the accuracy, overreliance, and ethical uses. Therefore, the integration into the EFL class needs careful consideration and guidance to maximize its potential and reduce challenges.